Possession consciousness, religious individualism, and subjectivity in Brazilian Umbanda. Issue 2 (3rd April 2017) - Espírito Santo, Diana
ABSTRACT: This article explores perceived changes in patterns of consciousness in relation to possession phenomena among a sector of urban practitioners of the Brazilian religion of Umbanda, and argues that these perceptions have been accompanied by the emergence of a more individualist approach to religious selfhood which aims to lay claim to a particular vision of Umbanda. These Umbandists understand their spirit universe in ontologically plastic terms, relativizing spirit identities much like Umbanda's founders. The increasing emphasis given to conscious forms of possession tallies with a relatively new attention to the self and its awareness of tradition, thought to be lacking in previous generations. This article also defends that we can produce an anthropological understanding of possession as having cosmogonic rather than just expressive effects.